MITIGASI BENCANA LONGSOR DI KAWASAN PERUMNAS BUKIT BERINGIN LESTARI, GONDORIYO, NGALIYAN, SEMARANG DENGAN MENGGUNAKAN VETIVER GRASS TECHNOLOGY - Raden Arfan Rifqiawan (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2015)
This action research is realized by the landslide disaster mitigation activities in the area of Perumnas Bukit Beringin Lestari, Gondoriyo, Ngaliyan Semarang using Vetiver Grass Technology. Implementation of Vetiver Grass Technology carried out with the active participation of citizens. Residents work together to mitigate landslide in their own environment. There are two stages in this activity. The initial stage, the residents asked the Perumnas as the developer to carry out re-installation of gabions and gabion installation at the disaster site. This is done so that subsequent landslides do not occur again. It was followed up a month later by the Perumnas. The next stage is, people install Vetiver Grass Technology in the former disaster areas to rehabilitate the degraded land and protect embankments, gabion, and building houses.